1992
DOI: 10.1093/milmed/157.7.334
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Stress Fracture in Young Army Women: Indications for Further Research

Abstract: Several factors which affect bone density and predict risk of osteoporosis (e.g., ethnic origin, amenorrhea) are reportedly associated with a higher incidence of stress fracture in active premenopausal women. The authors surveyed 2,312 active duty Army women for the prevalence of ever having been diagnosed ("told by a doctor") with a stress fracture (16.1% of respondents) and examined the relationship between surveyable risk factors for low bone density and this self-reported stress fracture history (self-repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 0 publications
3
59
1
Order By: Relevance
“…A study of female college athletes found that seven of 25 women with cases of stress fracture had a history of menstrual irregularity, while none of the 25 uninjured controls had such a history (127). A survey of 1,630 women in the US Army showed that those with a history of amenorrhea lasting more than 6 months were more likely to have experienced one or more stress fractures in their lifetime (prevalence ratio = 1.7, 95 percent CI: 1.2, 2.1) (128). While all of the civilian and military studies examining the association of amenorrhea and irregular menses with risk of stress fracture had some weaknesses in design and analyses, in the aggregate they strongly suggest that such an association exists.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…A study of female college athletes found that seven of 25 women with cases of stress fracture had a history of menstrual irregularity, while none of the 25 uninjured controls had such a history (127). A survey of 1,630 women in the US Army showed that those with a history of amenorrhea lasting more than 6 months were more likely to have experienced one or more stress fractures in their lifetime (prevalence ratio = 1.7, 95 percent CI: 1.2, 2.1) (128). While all of the civilian and military studies examining the association of amenorrhea and irregular menses with risk of stress fracture had some weaknesses in design and analyses, in the aggregate they strongly suggest that such an association exists.…”
Section: Demographic Factorsmentioning
confidence: 99%
“…In elite military training programs, exercise conditions can be considered to be reasonably uniform yet consistently a small fraction of trainees suffer stress fractures, and presumably these individuals have biomechanical differences that heighten their susceptibility. Because stress fractures are also more common in females 7,14 this would suggest that there may be gender differences in those susceptibility factors.…”
Section: Introductionmentioning
confidence: 99%
“…4 A large, cross-sectional survey of 2312 female active duty soldiers showed that a history of amenorrhea, smoking, white race, and a family history of osteoporosis were associated with a history of stress fracture. 18 In a case-control study, 27 female military recruits with stress fractures reported significantly higher levels of exercise and demonstrated lower femoral neck BMD than did 158 female subjects without fractures. 19 Few studies have been conducted with samples of adolescent athletes, and none have examined factors related to stress fractures among girls Ͻ17 years of age.…”
mentioning
confidence: 99%